(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The quality of earnings is one of the most controversial topics of financial management because of its modernity, and it represents one of the research breakthroughs in the field of financial sciences, because it led him to shift from the aspect of quantitative financial analysis to qualitative financial analysis, and that his study alongside investment efficiency added another dimension to the presentation of theories, logical relationships and research opinions. In line with the edges of financial knowledge, it formed a philosophical title that measured and analyzed the relationship between the quality of earnings and the efficiency of investment in companies. The quality of returns on investment efficiency through under- and over-investment, the quality of earnings was evaluated using the receivables quality model, and the rest of that model was relied upon, after which the parameter that expresses the quality of earnings, and the efficiency of investment in companies was evaluated using the multiple regression model that takes the size of the investment as A dependent variable, and the determinants of that efficiency are then independent variables, and the rest of that model was relied upon, after which the parameter T expresses the efficiency of investment, the negative residuals express a lack of investment, while the positive residuals express excessive investment. To other companies, as well as an indication of the impact of the quality of earnings on the efficiency of the study, and the results of the study showed that the quality of earnings has an impact on the efficiency of investment in the study sample companies.